Rice Dwarf Virus Small RNA Profiles in Rice and Leafhopper Reveal Distinct Patterns in Cross-Kingdom Hosts - Wang, Yu (Viruses, 2019)
RNA silencing has evolved as a widespread antiviral strategy in many eukaryotic organisms. Antiviral RNA silencing is mediated by virus-derived small RNAs (vsiRNAs), created by the cleavage of double-stranded viral RNA substrates by Dicer (Dcr) in animals or Dicer-like (DCL) proteins in plants. However, little is known about how the RNA silencing mechanisms of different hosts respond to the same virus infection. We performed high-throughput small RNA sequencing in Nephotettix cincticeps and Oryza sativa infected with Rice dwarf phytoreovirus and analyzed the distinct accumulation of vsiRNAs in these two hosts. The results suggested a potential branch in the evolution of antiviral RNA silencing of insect and plant hosts. The rice vsiRNAs were predominantly 21 and 22 nucleotides (nt) long, suggesting that OsDCL4 and OsDCL2 are involved in their production, whereas 21-nt vsiRNAs dominated in leafhopper, suggesting the involvement of a Dcr-2 homolog. Furthermore, we identified ~50-fold more vsiRNAs in rice than in leafhoppers, which might be partially attributable to the activity of RNA-dependent RNA polymerase 6 (RDR6) in rice and the lack of RDR genes in leafhoppers. Our data established a basis for further comparative studies on the evolution of RNA silencing-based interactions between a virus and its hosts, across kingdoms.